2019
DOI: 10.1371/journal.pbio.3000139
|View full text |Cite
|
Sign up to set email alerts
|

Potent anti-influenza H7 human monoclonal antibody induces separation of hemagglutinin receptor-binding head domains

Abstract: Seasonal influenza virus infections can cause significant morbidity and mortality, but the threat from the emergence of a new pandemic influenza strain might have potentially even more devastating consequences. As such, there is intense interest in isolating and characterizing potent neutralizing antibodies that target the hemagglutinin (HA) viral surface glycoprotein. Here, we use cryo-electron microscopy (cryoEM) to decipher the mechanism of action of a potent HA head-directed monoclonal antibody (mAb) bound… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 53 publications
1
32
0
Order By: Relevance
“…In addition, subtype-specific bnAbs that target the vestigial esterase subdomain [127,128], "lateral patch" epitope on HA1 [129], and the junction between the ectodomain and membrane anchor have also been identified [66]. In 2019, an H7-specific bnAb was shown to target an epitope that partly involves the HA protomer-protomer interface in HA1 [130]. Such a finding demonstrated that an antibody epitope does not need to be completely solvent exposed in the prefusion conformation.…”
Section: Antibodies To Influenza Hamentioning
confidence: 99%
“…In addition, subtype-specific bnAbs that target the vestigial esterase subdomain [127,128], "lateral patch" epitope on HA1 [129], and the junction between the ectodomain and membrane anchor have also been identified [66]. In 2019, an H7-specific bnAb was shown to target an epitope that partly involves the HA protomer-protomer interface in HA1 [130]. Such a finding demonstrated that an antibody epitope does not need to be completely solvent exposed in the prefusion conformation.…”
Section: Antibodies To Influenza Hamentioning
confidence: 99%
“…These intermediate states in viral entry are transient and thermodynamically unstable, making it impossible to understand these transitions using standard methods. Images of the simian virus 5 / parainfluenza virus 5 (SV5/PIV5) fusion protein intermediate state, triggered by heat and captured with a fusion-inhibitory peptide, were examined using negative stain EM [85]; more recently, multiple intermediate states of influenza hemagglutinin (HA), including the first structures of an extended trimer state, were solved using cryo-EM [43,87]. These rarely visualized transition states are significant for fundamental understanding of the viral entry process.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…While well-characterized for influenza [43][44][45][46] and HIV [47][48][49][50][51][52], the structural organization of glycoproteins and their architecture on HPIV3 viral surfaces is largely unknown [1,11]. The 3-dimensional structure of the F fusion trimer from multiple paramyxoviruses, including HPIV3, has been described in both the pre-fusion and post-fusion forms [12,[53][54][55][56].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, H7 was found to interact with another HA head hidden epitope that is only partly and transiently exposed in the prefusion conformation. These findings suggest that the HA trimer possesses a conformational dynamics in which different prefusion conformations (breathing) briefly expose cryptic epitopes that can be targeted by protective antibodies (Turner et al, 2019). This breathing phenomenon has also been observed in other viruses, including HCoV spike, and could help to identify new conserved sites of vulnerability (Yuan et al, 2017;Wrapp et al, 2020).…”
Section: Learning From Other Pandemic Virusesmentioning
confidence: 65%